2020
DOI: 10.1371/journal.pone.0230129
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of clinically relevant and robust fMRI-based language lateralization: Choosing the laterality index calculation method

Abstract: The assessment of language lateralization has become widely used when planning neurosurgery close to language areas, due to individual specificities and potential influence of brain pathology. Functional magnetic resonance imaging (fMRI) allows non-invasive and quantitative assessment of language lateralization for presurgical planning using a laterality index (LI). However, the conventional method is limited by the dependence of the LI on the chosen activation threshold. To overcome this limitation, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Lateralisation can also be inferred from rates of aphasia after cerebral lesions [6]. fMRI laterality indices have used various approaches, reflecting differences in threshold and the number and particular voxels included [208], with LI-tool being a popular method [209]. In one study using whole hemispheres, the majority of participants showed left-hemisphere dominance (67/82; 81.7%), with a higher rate of left-hemisphere dominance amongst right-handers than lefthanders [210].…”
Section: Laterality Coefficients For Assessment Of Language Lateralis...mentioning
confidence: 99%
“…Lateralisation can also be inferred from rates of aphasia after cerebral lesions [6]. fMRI laterality indices have used various approaches, reflecting differences in threshold and the number and particular voxels included [208], with LI-tool being a popular method [209]. In one study using whole hemispheres, the majority of participants showed left-hemisphere dominance (67/82; 81.7%), with a higher rate of left-hemisphere dominance amongst right-handers than lefthanders [210].…”
Section: Laterality Coefficients For Assessment Of Language Lateralis...mentioning
confidence: 99%
“…The PLI was compared between BA and V1 and between BA and HM using the one‐tailed Mann‐Whitney U test. In defining the PLI, we followed the logic of the standard method of defining laterality index (LI) used for analyzing tbfMRI data 36,47,48 …”
Section: Methodsmentioning
confidence: 99%
“…46 The samples were assumed to be independent; hence, the nonparametric one- followed the logic of the standard method of defining laterality index (LI) used for analyzing tbfMRI data. 36,47,48 In order to compare the distribution of power across frequencies, the number of peaks within 25% of the maximum peak were identified for the BA, HM, and V1 power spectra by adding the corresponding number of peaks from the left and right hemispheres. 46 The one-tailed Mann-Whitney U test was applied to determine the statistical significance of the difference between the number of peaks for BA and V1…”
Section: Power Spectrum Analysis and Statisticsmentioning
confidence: 99%
“…Not surprisingly, a survey showed that 79% of 63 epilepsy surgical programs used statistical thresholding that varied by the patient [63]. Several approaches have been proposed to calculate threshold-independent LI in the clinical setting, including a recent simplified method of LI calculation [22]. (b) Number and type of language tasks-lateralization patterns of language may change depending on the type of task used [11,13,64].…”
Section: The Confounds Of Fmri Analysismentioning
confidence: 99%
“…As will be presented below, different approaches to an fMRI analysis can significantly alter the LI values in a single subject. The approaches include using threshold-dependent versus threshold-independent calculations [22,23], applying a full-hemisphere versus an region of interest (ROI) approach [24,25], and administering a single task versus a panel of language tasks [11].…”
Section: Introductionmentioning
confidence: 99%